2014
DOI: 10.1063/1.4898389
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optical property in quaternary GaInAsSb/AlGaAsSb quantum wells

Abstract: Articles you may be interested inCarrier localization and in-situ annealing effect on quaternary Ga1−xInxAsySb1−y/GaAs quantum wells grown by Sb pre-deposition Appl. Phys. Lett. 102, 113101 (2013); 10.1063/1.4795866Much improved flat interfaces of In Ga As ∕ Al As Sb quantum well structures grown on ( 411 ) A InP substrates by molecular-beam epitaxya)Photoluminescence and photoreflectance study of InGaAs/AlAsSb quantum wells grown by molecular-beam epitaxy J. Appl. Phys. 95, 1050 (2004); 10.1063/1.1637936Optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The insert in figure 4(c) gives the Arrhenius plots of the integrated PL intensity versus inverse temperature, and a thermally activated process was observed with an activation energy of 134 meV. We demonstrate that the PL intensity dropping as the temperature increasing was probably due to the carriers tending to escape from the nanosheets, thus resulting in a higher activation energy barrier and a lower probability for photo-induced emission [26]. Based on the DFT, an accurate knowledge of conduction and valence bands topology enables the identification of alloy compositions, where carrier transition style and lifetime are likely to be found for specific bandgap and lattice parameters [14,49].…”
Section: Resultsmentioning
confidence: 69%
“…The insert in figure 4(c) gives the Arrhenius plots of the integrated PL intensity versus inverse temperature, and a thermally activated process was observed with an activation energy of 134 meV. We demonstrate that the PL intensity dropping as the temperature increasing was probably due to the carriers tending to escape from the nanosheets, thus resulting in a higher activation energy barrier and a lower probability for photo-induced emission [26]. Based on the DFT, an accurate knowledge of conduction and valence bands topology enables the identification of alloy compositions, where carrier transition style and lifetime are likely to be found for specific bandgap and lattice parameters [14,49].…”
Section: Resultsmentioning
confidence: 69%
“…The value of α between 1 and 2 is well known for exciton-like transition, whereas less than 1 indicates free-to-bound and donor-acceptor transitions. [37][38][39] From the abovementioned analysis, it is confirmed that P2 is an emission related to localized carriers. The localized carriers were confined by indium cluster located at the interface between the barriers and the wells in the QW structure, due to segregation of indium in an InGaAsSb layer during the growth of AlGaAsSb barrier layers.…”
Section: Resultsmentioning
confidence: 74%
“…Although our device structure is quite similar to that previously reported in reference [14], we use this further for electrically pumped PCSEL fabrication. The key technique [20] by controlling the Group-V elements at interfaces is also opted to enhanced the optical properties in quaternary GaInAsSb/AlGaAsSb quantum wells in this manuscript. However, our previous work [14,20] only stopped at optically pumped PCSEL performance.…”
Section: Resultsmentioning
confidence: 99%
“…The key technique [20] by controlling the Group-V elements at interfaces is also opted to enhanced the optical properties in quaternary GaInAsSb/AlGaAsSb quantum wells in this manuscript. However, our previous work [14,20] only stopped at optically pumped PCSEL performance. The performance difference between this manuscript and our previous work is owing to the different conditions of our MBE system.…”
Section: Resultsmentioning
confidence: 99%